Learning of core science subject in English of upper secondary level : a study among form four non-science students - Richard B, Simon (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This study aims to explore and identify non-Science students' attitudes and perceptions towards learning Core Science in English in their upper secondary level of schooling. The particular group of participants selected for this study were the pioneering batch of students who were the first to experience the policy shift in the change of medium of instruction in the teaching and learning of Mathematics and Science subjects from Malay to English. The study applied quantitative survey research design with the use of single-method approach in data collection, which is questionnaire. A total of 185 participants from both urban and rural schools participated in the study and their responses towards the statements in the questionnaire were analysed and evaluated to answering the research questions. From the results, it is found out that rural participants generally have positive attitudes towards learning of Core Science in English, while urban counterparts were otherwise. Regardless of these attitudes, both groups of participants were perceptive towards the advantages, problems, as well as opportunities they encounter during the process of learning the subject. Furthermore, the participants' responses towards language preference in the learning of Core Science is also a point worth considering in understanding their overall attitudes and perceptions towards the language shift in medium of instruction. Therefore, the study has able to shed some light into the students' point of view towards the impact, challenges and problems faced in regard to the change of learning landscape and hopefully will further create better understanding and awareness among the public and educational practitioners at large upon the current issues gravitating around education.